2023
DOI: 10.1111/jgs.18269
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and incident disability and mortality among frail older adults: A JAGES longitudinal study

Abstract: Background Frailty is the highest risk factor for incident disability and mortality. Social participation is a modifiable factor for reducing adverse outcomes among independent older adults. However, the association between social participation and incident disability and mortality among frail older adults remains unclear. Therefore, we examined the association between various social activities and incident disability and mortality. Methods This nationwide prospective cohort study (The Japan Gerontological Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(84 reference statements)
2
8
0
Order By: Relevance
“…[24][25][26][27] Furthermore, it has been reported that high levels of social participation and engagement in hobbies can also contribute to the prevention of disability among older adults. 11,12,28 We have reaffirmed the importance of social participation in frailty prevention, as demonstrated by numerous previous studies and our own research during the COVID-19 pandemic. Previous studies conducted during the COVID-19pandemic have shown that individuals who have less interaction with their neighbors are at a higher risk of developing frailty.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[24][25][26][27] Furthermore, it has been reported that high levels of social participation and engagement in hobbies can also contribute to the prevention of disability among older adults. 11,12,28 We have reaffirmed the importance of social participation in frailty prevention, as demonstrated by numerous previous studies and our own research during the COVID-19 pandemic. Previous studies conducted during the COVID-19pandemic have shown that individuals who have less interaction with their neighbors are at a higher risk of developing frailty.…”
Section: Discussionsupporting
confidence: 78%
“…It is clear that hobbies and community activities reduce the risk of disability and death in older people with frailty, that participation in neighborhood associations as a community activity has a positive impact, and that duplicating cultural and community activities are associated with the prevention of frailty. [11][12][13] However, many of these activities were limited as a result of the COVID-19 pandemic. This led us to hypothesize that the continuation of hobbies and community activities might be key factors in preventing frailty even during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Covariates used in the questionnaire survey covered a wide range of variables that would predict functional decline, that is, demographic, lifestyle‐related, and health‐related variables based on systematic reviews 22,23 and articles related to working and incidence of disability 4–7,24 …”
Section: Methodsmentioning
confidence: 99%
“…Covariates used in the questionnaire survey covered a wide range of variables that would predict functional decline, that is, demographic, lifestyle-related, and health-related variables based on systematic reviews 22,23 and articles related to working and incidence of disability. [4][5][6][7]24 The covariates particularly included age, sex, living situation (living with others or alone), and educational level (junior high school, high school, or junior college/vocational college/college/ graduate school graduate). Equivalent income was calculated by dividing household income by the square root of the number of household members (<1.2, ≥1.2 million yen).…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation